Malaysia : Sustainable Adoption of Innovative Channels for Financial Inclusion - World Bank (Washington, DC, 2014)
This note focuses on the regulatory and market environment relevant to the emergence and adoption of innovative delivery channels to promote greater financial inclusion in Malaysia. Financial inclusion is defined here not only as providing access to financial services, but also as enabling and promoting increased usage of those services. Achieving higher levels of access and usage requires an extensive and efficient retail payments infrastructure, affordable financial products that meet the needs of customers, and actions to address cultural and social factors that influence customers' choices. This note therefore considers the implications for financial inclusion of Malaysia's evolving retail payments landscape and the country's potential to go beyond providing physical access to services. Malaysia has achieved remarkable progress in providing access to basic bank accounts to the majority of the population and credit to small and medium enterprises. Increasing access and usage will depend, to a large extent, on greater availability of technology-enabled channels that go beyond brick-and-mortar branches and leverage on existing third-party infrastructure such as retailers and neighborhood shops, which are usually referred to as 'retail agents.' There are only a few regulatory obstacles for the use of agents by banks (there is already an enabling framework for nonbanks) and for development of other alternative delivery modes. Relevant regulation is generally permissive while maintaining minimum standards for the safety and security of transactions and the protection of users. Financial inclusion is defined in this Note as a situation where financial services are not only readily accessible, but also widely used by the majority of the population in meeting all or most of their financial needs. After a brief overview of the state of access to basic financial services and the institutional potential for expansion in Malaysia, the note analyzes the market environment and the policy and regulatory frameworks that may have an impact on the emergence and sustainability of delivery modes that could cater to underserved and un-served communities.